Effect of glycerol monostearate on the gelatinization behavior of maize starches with different amylose contents - Garcia, Marina Costa [UNESP] (2015)
The effect of different concentrations (1, 2, and 3%w/w) of glycerol monostearate (GMS) on gelatinization behavior of normal maize starch (NMS), waxy maize starch (WMS), and high amylose maize starch (HAMS) was evaluated. Leaching of amylose and solubility decreased in all starches with added GMS. Gelatinization temperatures increased in NMS but there was no change in WMS. During first heating in DSC, only NMS with added GMS displayed the dissociation peak of amylose-lipid complex. In cooling the exothermic peaks (approximate to 74 degrees C) confirmed the recrystallization of inclusion complexes in NMS and HAMS. In second heating, the complex enthalpy increased in NMS and HAMS while WMS with added GMS did not display any transition peak of inclusion complex. Pasting temperature increased in NMS and was not altered in WMS as GMS was added. Addition of GMS decreased retrogradation and syneresis, and increased paste transparency in NMS and WMS. The results indicated inclusion complex formation in NMS and HAMS. The whole emulsifier amount complexed with amylose in NMS when 1% GMS was added, while 3% GMS was necessary in HAMS. A slight increase in paste viscosity at approximate to 70 degrees C during cooling among the decrease in leached amylose, solubility, retrogradation, and gelatinization enthalpy evidenced interactions between few amylose molecules and/or longer amylopectin branched chains with GMS in WMS.